ACE2 gene polymorphisms and invasively measured central pulse pressure in cardiac patients indicated for coronarography - Vašků, Anna; Bienertová-Vašků, Julie; Pařenica, Jirí; Goldbergová, Monika Pávkova; Lipková, Jolana; Zlámal, Filip; Kala, Petr; Spinar, Jindřich (Journal of the renin-angiotensin-aldosterone system, 2013)
BACKGROUND AND AIM: The objective of this research was to determine whether invasively measured central pulse pressure (PP) in patients indicated for coronarography is associated with two common polymorphisms in the ACE2 region (rs4646156 and rs4646174). METHODS: A total of 307 patients were enrolled in the study. The genotyping of both SNPs from peripheral blood samples was carried out using 5'exonuclease (Taqman®) chemistry on the ABI Prism® 7000 system (Applied Biosystems, Foster City, CA, USA). RESULTS: In both polymorphisms, the associations with central PP were found to be highly significant when all five possible genotypes in the population had been compared (p = 0.0001). In men, there was a higher incidence of previous myocardial infarction in G0 genotype carriers of rs54646174 (OR ratio = 7; p = 0.005). The AA genotype of rs4646156 had a 7.81× higher risk of severe angina pectoris in women (OR = 7.81, p = 0.05). A significant difference in allelic frequency of ACE2rs4646174 was found between women with and without significant stenoses of the circumflex branch of the left coronary artery. CONCLUSION: More research into the role of ACE2 genetic variability in PP regulations is necessary for more detailed physiological and pathophysiological comprehension of PP regulation.
Keywords: dospělí; Angiotensin-Converting Enzyme 2; Female; angiotensin konvertující enzym; ACE2; multivariační analýza; Adult; ženské pohlaví; jednonukleotidový polymorfismus; Multivariate Analysis; lidé; pulz; Polymorphism, Single Nucleotide; genetická predispozice k nemoci; Aged, 80 and over; Genetic Predisposition to Disease; koronární angiografie; krevní tlak; Peptidyl-Dipeptidase A; Humans; Male; angiotensin-konvertující enzym 2; Aged; Cardiovascular Diseases; polymorphism; kardiovaskulární nemoci; pulse pressure; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; severity; Blood Pressure; Pulse; Demography; Middle Aged; demografie; Coronary Angiography